2013
DOI: 10.5897/ijsa2013.0448
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic profile of people living with HIV/AIDS (PLWHA) in Idoma land, Benue state, North-central Nigeria: Implications for HIV/AIDS control

Abstract: The profile of PLWHA constitutes a subject of interest in HIV/AIDS control initiatives. This study investigated the socio-demographic attributes of PLWHA in Idoma land, Benue State [Nigeria], with a view to suggesting customized measures for HIV/AIDS control. A total of 133 PLWHA and 25 relatives of PLWHA selected from two HIV/AIDS treatment centres provided the data through a survey questionnaire. Health workers and community/group leaders similarly provided information through IDIs and FGDs on their percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In comparing the 6-months period of the PITC implementation in our facility with the epoch (one year) pre-implementation using the VCT approach, the PITC strategy appears to be more effective in the hospital environment. Consistent with previous studies from Benue state Nigeria [ 21 , 22 ], this study found a higher prevalence of HIV testing among participants who had primary/secondary education compared to those who had no schooling. In addition, the PITC strategy provided information on HIV transmission and prevention (during the pre- and post-test counseling) to the patients and the community.…”
Section: Resultssupporting
confidence: 92%
“…In comparing the 6-months period of the PITC implementation in our facility with the epoch (one year) pre-implementation using the VCT approach, the PITC strategy appears to be more effective in the hospital environment. Consistent with previous studies from Benue state Nigeria [ 21 , 22 ], this study found a higher prevalence of HIV testing among participants who had primary/secondary education compared to those who had no schooling. In addition, the PITC strategy provided information on HIV transmission and prevention (during the pre- and post-test counseling) to the patients and the community.…”
Section: Resultssupporting
confidence: 92%
“…Almost two-third of respondents was married (67.3%), and most married respondents were in monogamous relationships. Many of the female respondents were married with or without children; similar results were reported in some local studies (Afolabi et al, 2015;Anyebe et al, 2019;Adebayo et al, 2017). Extramarital relationship was a norm among many married ethnocultural groups in the study area.…”
Section: Marital Statussupporting
confidence: 85%
“…However, Anyebe et al (2019) found secondary education as the highest educational qualification due to 2019) reported participants that were mostly business men and women, only a few of them had formal education; a similar finding was also reported by Shittu et al (2016), Adebayo et al (2017) reported an increasing HIV prevalence with higher educational attainment. Therefore, a high level of educational status may not necessarily suggest a low HIV prevalence as shown in the present study.…”
Section: Level Of Educationsupporting
confidence: 70%
See 1 more Smart Citation
“…The Idoma were chosen for this study owing to the low prevalence of modern contraceptive use in North Central Nigeria (NPC and ICF Macro, 2014). Moreover, other demographic and health issues such as the fertility rate, maternal mortality, HIV/AIDS and other sexually transmitted infections have been reported to be high among the group (Anyebe et al, 2013; Obogo, 2013).…”
Section: Methodsmentioning
confidence: 99%